Integrated theoretical framework in assessing teachers' innovative behaviour in Malaysia - Johari, Aduni (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
By year 2017, all form one students in the government secondary schools shall be enjoying learning under the new curriculum of Kurikulum Standard Sekolah Menengah (KSSM) set by the Ministry of Education (MOE) as continuation of these students being the pioneer in the Kurikulum Standard Sekolah Rendah (KSSR) which was introduced in year2011. One of the aims in the Standard-Based English Language Curriculum for Secondary Schools (SBELC) of Form 1 2017, is preparing the students in collaborating with others to solve problems creatively and innovatively in the real world. Hence, the educators need to exhibit innovative behaviour to nurture the students in a smooth and systematic manner in accordance top the MOE philosophy. Under the National Philosophy, the education system is designed to produce citizens who are apart from being knowledgeable and competent, yet also able to contribute to the betterment of the nation at large. Therefore, this conceptual paper is prepared to develop a theoretical framework for assessing the teachers’ innovative behaviour in several public schools in Malaysia. The major latent factors that have analytical potential of teacher’s innovative behaviour are perceived supervisory support and teamwork. The theoretical foundation used for this study is the integration of theory of strong and weak ties, theory of planned behaviour and stage model of innovative behaviour.